Effect of hyperoxic-supplemented interval training on endurance performance in trained cyclists - Kilding, A. E.; Wood, M.; Sequira, G.; Bonetti, D. L. (International Journal of Sports Medicine, 2012)
The aim of this study was to determine the effect of hyperoxic-supplemented interval training on endurance performance. Using a single-blind, randomised control-trial design, 16 well-trained cyclists were randomly assigned to either hyperoxic or normoxic training. Participants visited the laboratory twice per week, for 4 weeks, to perform high-intensity interval training sessions. A 20 km TT, incremental exercise test and 60s all-out test were conducted pre- and post-intervention. Smaller effects for most physiological measures, including VO2peak (1.9±4.3%) and lactate threshold (0.3±8.3%), were observed after training in hyperoxia compared to normoxia. There was a small increase in mean power during the 20 km TT after hyperoxia [2.1±3.7%; effect size (ES): - 0.30±0.39] but this was less than that observed after normoxia (4.9±3.9%; ES: - 0.44 ± 0.60). During the 60 s all-out test, the peak relative power was relatively unchanged, whereas mean relative power was increased in normoxia (2.3±3.4%) but not hyperoxia (0.3±1.2%; ES: - 0.34 ± 0.49). Hyperoxic-supplemented interval training in the competitive season had less effect on endurance and high-intensity performance and physiology in trained endurance cyclists compared to interval training in normoxia. Therefore hyperoxic-supplemented training at sea level appears to be not worthwhile for maximising performance in competitive endurance athletes.